2013
DOI: 10.5935/1981-2965.20130021
|View full text |Cite
|
Sign up to set email alerts
|

Use of herbal medicines in control of gastrointestinal nematodes of small ruminants: efficacies and prospects

Abstract: It is mainly due to the resistance to conventional anthelmintics representing a barrier, being a constant challenge to search for new bases in the control of these parasites.Thus the use of phytotherapics becomes viable alternative in the fight against gastrointestinal nematodes, beyond promoting slow development of the resistance, it is biodegradable and does not cause environmental contamination. Thereby, the review aims to address the main results obtained in research on herbal drugs effective in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Nevertheless, the finding that there were no observed toxic effects on tested animals allows an opportunity for an increased dose in future trials to reach a higher efficacy. The obtained results and demonstrated efficacy should not be neglected since they suggest that these plant products, coupled with other methods, may still play a significant role in an integrated approach for nematode control in ruminants, in case they are proven ineffective as independent products [40,41]. Furthermore, our research group has already made new experimental efforts with the evaluation of the in vivo efficacy of other highly effective in vitro EOs from the present study (data not shown).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Nevertheless, the finding that there were no observed toxic effects on tested animals allows an opportunity for an increased dose in future trials to reach a higher efficacy. The obtained results and demonstrated efficacy should not be neglected since they suggest that these plant products, coupled with other methods, may still play a significant role in an integrated approach for nematode control in ruminants, in case they are proven ineffective as independent products [40,41]. Furthermore, our research group has already made new experimental efforts with the evaluation of the in vivo efficacy of other highly effective in vitro EOs from the present study (data not shown).…”
Section: Discussionmentioning
confidence: 71%
“…Firstly, EOs have a rich chemical composition of various bioactive compounds with huge pharmacological potential [14], which can lead to high activity against nematodes, as shown in our in vitro study. Furthermore, a large number of compounds in EOs that belong to different chemical classes may contribute to a reduced susceptibility to resistance [14,41]. Some reports state that botanical anthelmintics may be considered well tolerated by animals from the toxicology perspective and are related to the low amount of residues in meat and milk [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The leaves have phytotherapeutic properties against oxidative stress, diabetes, neuralgia, arthritis, malaria, in ammation, tumours and cancer. In addition, several studies have shown that soursop has an anthelmintic effect against parasites of small ruminant animals [6,7,8]. Some studies demonstrated the nematicidal and antifungal activities of acetogenins isolated from Annonaceae, making these compounds a promising source for new molecules for the development of potential botanical nematicides and fungicides [9].…”
Section: Introductionmentioning
confidence: 99%